NOTES ON THE CONTRASTING CONCEPTS OF ACCOUNTING AND ECONOMICS. - Saliers, Earl A. (The Accounting Review, 1941)
Accounting and economics are generally considered to be social sciences and accounting is generally regarded as a branch of economics. Wealth is the subject-matter of both sciences, but whereas economics is thought of as the science of wealth, accounting is restricted to the devising of records which will reflect the status of wealth and changes which take place in wealth of a given business unit-whether sole proprietorship, partnership, or corporation. The difference in the manner in which wealth is considered by these two sciences undoubtedly accounts, to a large degree, at least, for the seeming inconsistencies which appear in their literature. With allowance for exceptional cases economist and accountant agree that most expenditures and most efforts placed on the production of commodities result in income. An accountant keeps records for one individual or enterprise. Income is produced during the manufacturing process, but title to this income cannot be said to rest definitely in any individual or group until the goods manufactured have been sold.